Should AFP (or any biomarkers) be used for HCC surveillance? - Ahmed Mohammed, Hager F. (Curr Hepatol Rep, 2017)
A) PURPOSE OF REVIEW: To address the controversy around the use of biomarkers for hepatocellular carcinoma (HCC) surveillance in individuals with cirrhosis or chronic hepatitis B who are at risk for development of liver cancer. B) RECENT FINDINGS: Recent studies suggest that surveillance for hepatocellular carcinoma is beneficial, even after adjustment for lead time and other biases. Alpha fetoprotein (AFP) is complementary to ultrasound (US) in surveillance, particularly in obese patients and patients with infiltrative tumors. US and AFP are both associated with harms to patients from false positive over-diagnosis, with US appearing to cause greater harms. Including patient demographic characteristics and additional biomarkers into diagnostic models is beneficial. Recent studies emphasize the advantage of time trends in biomarkers over single cross-sectional measurements. C) SUMMARY: AFP and other biomarkers are complementary to US in surveillance for HCC, especially when applied in models including patient variables and incorporating time trends in biomarker levels. With advances in genetic and molecular analysis of tumors, we may be poised at the cusp of a revolution in HCC surveillance.